Performance-Shaping Factors of Personnel Performing Evacuation and Escape on Offshore Installations in Tropical - Norazahar, Norafneeza; Morshidi, Nur Azizah Arryanie; Ahmad, Arshad; Ali, Wijayanuddin Mohd (UI Scholars Hub, 2020)
Performance-shaping factors (PSFs) are used to address the strengths and weaknesses of workers performing escape and evacuation activities. These PSFs are time, environmental factors as stressors, complexity of activities, experiences and training, interaction between workers and emergency equipment, workers’ physical conditions, and procedures. This paper presents a survey work on fitness for the duty of workers performing basic offshore survival and emergency response training. The training provides credible scenarios of escape and evacuation in case of an emergency of offshore installations in tropical waters. The survey is conducted among participants of the tropical basic offshore safety induction & emergency training with emergency breathing system. Sixteen participants of the training voluntarily answered the set of questionnaires. The survey work addresses the fitness for duty among workers performing escape and evacuation on offshore installations. Survey results indicate that workers must have good physical conditions and mental fitness in order to accomplish the escape and evacuation activities.